The depression of a graph - Cockayne E.J.; Geldcnhuys G.; Grobler P.J.P.; Mynhardt C.M.; Van Vuuren J.H. (Utilitas Mathematica, 2006)
The notions of the flatness of an edge-ordering and of the depression of a simple graph are introduced. Some general properties of these parameters are established, after which a characterisation of graphs with depression two is given and exact values for the depression parameter of a number of simple graph classes are found and contrasted with those of a previously established parameter, called the altitude of a graph (which is in a sense the dual to the depression parameter).